Active tectonics in the central and eastern Betic Cordillera through morphotectonic analysis: the case of Sierra Nevada and Sierra Alhamilla - Azañón, J. M.; Pérez-Peña, J. V.; Giaconia, F.; Booth-Rea, G.; Martínez-Martínez, J. M.; Rodríguez-Peces, M. J. (Journal of Iberian Geology, 2012)
Quaternary activity of folds and faults can be assessed by the analysis of drainage network and the evaluation of geomorphic indexes. These analyses are especially productive in semiarid areas where tectonic rates are low-to-moderate and Quaternary dating is limited. In this work, we have revisited the most relevant GIS-based methodologies used to assess tectonic activity by using morphometric analyses and we discuss the tectonic implications in two key areas of the central and eastern Betic Cordillera (Sierra Nevada and Sierra Alhamilla regions). In the Sierra Nevada area, the use of geomorphic indexes in the mountain range and in the neighboring Granada and Guadix-Baza basins suggests that all are part of the same SW-directed extensional system. The Granada basin (except in its NE border) subsided during the Late Pleistocene as it is located in the hanging wall of the extensional system. On the other hand, the Sierra Nevada mountain range, the NE border of the Granada basin and the Guadix-Baza basin are located in the active uplifted foot wall of the system. Thus, the higher fluvial incision rates in the Guadix-Baza basin can be directly correlated with the most recent uplift history of Sierra Nevada mountain range. In the Sierra Alhamilla region, a geomorphic study shows Late Pleistocene activity along the North Alhamilla Reverse Fault and the dextral transpressive South Gafarillos Fault, two segments of the Polopos Fault Zone, previously considered as an inactive fault.